2014
DOI: 10.1515/ncrs-2014-9047
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the trinuclear complex hexachlorido-1κ3Cl,3κ3Cl-bis(µ2-dimethylphosphorylmethanamine-1:2κ2N:O,3:2κ2N:O)- bis(dimethylphosphorylmethanamine-2κ2N,O)trizinc(II), C12H40Cl6N4O4P4Zn3

Abstract: C 12 H 40 Cl 6 N 4 O 4 P 4 Zn 3 ,monoclinic, C2/c (no. 15), a =16.8933(5) Å, b =9.1740(4) Å, c =21.5013(7) Å,Source of material 0.78 g(7.17 mmol)(Dimethylphosphoryl)methanamine (dpma) wasdissolved in basicethanol(p.a.,adjustedtopH8-9 by an ammonium hydroxide solution (20%),1,5 ml). To get amolar ratio of 3:4 zinc(II)chloride : dpma,0.73 g(5.38 mmol) zinc(II)chloride was added to the solution. The reaction mixture was heated to 50°C and stirred for 2h.Cooling to room temperature yielded in a viscose liquid. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that dpma is a potent bidentate ligand stabilizing mononuclear [3][4][5] and oligonuclear [6] complexes as well as coordination polymers [7]. In recent years, we have shown that the N-protonated dpmaH + cation is an excellent monodentate ligand.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, it has been shown that dpma is a potent bidentate ligand stabilizing mononuclear [3][4][5] and oligonuclear [6] complexes as well as coordination polymers [7]. In recent years, we have shown that the N-protonated dpmaH + cation is an excellent monodentate ligand.…”
Section: Introductionmentioning
confidence: 94%